Host-Induced Gene Silencing of a Sclerotinia sclerotiorum oxaloacetate acetylhydrolase Using Bean Pod Mottle Virus as a Vehicle Reduces Disease on Soybean - McCaghey, Megan; Shao, Dandan; Kurcezewski, Jake; Lindstrom, Ally; Ranjan, Ashish; Whitham, Steven A.; Conley, Shawn P.; Williams, Brett; Smith, Damon L.; Kabbage, Mehdi (Frontiers in Plant Science, 2021)
A lack of complete resistance in the current germplasm complicates the management of Sclerotinia stem rot (SSR) caused by Sclerotinia sclerotiorum in soybean. In this study, we used bean pod mottle virus (BPMV) as a vehicle to down-regulate expression of a key enzyme in the production of an important virulence factor in S. sclerotiorum, oxalic acid (OA). Specifically, we targeted a gene encoding oxaloacetate acetylhydrolase (Ssoah1), because Ssoah1 deletion mutants are OA deficient and non-pathogenic on soybean. We first established that S. sclerotiorum can uptake environmental RNAs by monitoring the translocation of Cy3-labeled double-stranded and small interfering RNA (ds/siRNAs) into fungal hyphae using fluorescent confocal microscopy. This translocation led to a significant decrease in Ssoah1 transcript levels in vitro. Inoculation of soybean plants with BPMV vectors targeting Ssoah1 (pBPMV-OA) also led to decreased expression of Ssoah1. Importantly, pBPMV-OA inoculated plants showed enhanced resistance to S. sclerotiorum compared to empty-vector control plants. Our combined results provide evidence supporting the use of HIGS and exogenous applications of ds/siRNAs targeting virulence factors such as OA as viable strategies for the control of SSR in soybean and as discovery tools that can be used to identify previously unknown virulence factors.